Komunikasi Lintas Budaya di Gereja Katolik Hati Kudus Tuhan Yesus Ganjuran Yogyakarta - Prameswari, Darlyss Charolina Eva; Azeharie, Suzy (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Hati Kudus Tuhan Yesus Ganjuran Catholic Church (HKTY Ganjuran Church) is a Catholic church located in Ganjuran Hamlet, Sumbermulyo Village, Bambanglipuro Sub-district, Bantul, Yogyakarta, which is part of the Archdiocese of Semarang. The church is designated as a cultural heritage site due to its strong connection to Javanese culture and historical value. This research aims to explore the acculturation that occurs between Javanese culture and the Catholic Church through cross-cultural communication at the HKTY Ganjuran Church and to identify the forms of Javanese cultural acculturation that take place at the HKTY Ganjuran Church. The theoretical frameworks employed in this study are integrative communication theory and cultural acculturation theory. The research adopts a qualitative descriptive approach with an ethnographic method. Data is collected through interviews, observations, documentation, literature reviews, and online data searches. The conclusion of this research is that Javanese cultural acculturation at the HKTY Ganjuran Church occurs through cross-cultural communication and cultural adaptation processes facilitated by integrative communication influenced by personal communication factors, host social communication, and the environment. The acculturation model in the HKTY Ganjuran Church involves integration with various forms of acculturation between Javanese culture and the Catholic Church, encompassing language, arts, customs, as well as the church's architecture and ornaments. Gereja Katolik Hati Kudus Tuhan Yesus Ganjuran (Gereja HKTY Ganjuran) merupakan gereja Katolik yang berlokasi di Dusun Ganjuran, Desa Sumbermulyo, Kecamatan Bambanglipuro, Bantul, Yogyakarta yang merupakan bagian dari Keuskupan Agung Semarang. Gereja tersebut dijadikan sebagai salah satu cagar budaya karena lekat akan kebudayaan Jawa serta memiliki nilai historis. Penelitian ini bertujuan untuk mengetahui akulturasi yang terjadi pada budaya Jawa dengan Gereja Katolik karena komunikasi lintas budaya yang terjadi di Gereja HKTY Ganjuran dan untuk mengetahui bentuk-bentuk akulturasi budaya Jawa yang terjadi pada Gereja HKTY Ganjuran. Teori yang digunakan dalam penelitian ini adalah Integrative Communication Theory dan Teori Akulturasi Budaya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode etnografi. Data penelitian diperoleh melalui wawancara, observasi, dokumentasi, studi pustaka dan penelusuran data online. Kesimpulan dari penelitian ini adalah akulturasi budaya Jawa di Gereja HKTY Ganjuran dapat terjadi karena terjalinnya komunikasi lintas budaya melalui proses adaptasi budaya melalui integrative communication yang dipengaruhi oleh faktor personal communication, host social communication dan environment. Model akulturasi yang terjadi di Gereja HKTY Ganjuran adalah integrasi dengan bentuk-bentuk akulturasi antara budaya Jawa dan gereja Katolik yang meliputi bahasa, kesenian, adat istiadat serta bangunan dan ornamen gereja.